(untitled) (Studia theodisca, 2019)
Review of Marco Castellari’s book Hölderlin und das Theater. Produktion – Rezeption – Transformation (2018), by Luca Crescenzi. Review of Marta Vero’s book Quella non comune tendenza all’universalità. Studio sull’«Empedocle» di Hölderlin (2018), by Giulia Puzzo. Review of Peter Utz’s book «Nachreife des fremden Wortes». Hölderlins «Hälfte des Lebens» und die Poetik des Übersetzens (2017), by Marco Castellari